Students’ Perception of Autonomous English Learning - Volya, Duti; Hadiyanto, Hadiyanto; Haryanto, Eddy; Abrar, Mukhlash (International Journal of Language Teaching and Education, 2025)
This study explores Indonesian EFL students' perceptions of autonomous learning within the context of the English Language Study Program at Universitas Jambi. Situated within national education reforms such as Merdeka Belajar Kampus Merdeka (MBKM), which emphasize learner independence and flexibility, the research investigates how autonomy is understood and practiced by students in a system traditionally bound by rigid curricula and teacher-centered approaches. Employing a mixed-methods design, the study surveyed 45 students using a validated autonomy self-assessment questionnaire and conducted follow-up interviews with selected participants. Quantitative results reveal that students demonstrate moderately high levels of autonomy, particularly in understanding instructional objectives and setting personal study plans. However, challenges remain in aligning personal learning goals with formal syllabi and sustaining independent learning beyond curricular demands. Qualitative findings enrich these insights, highlighting students' proactive behaviors in time management and self-directed learning, yet also uncovering a reliance on teacher direction and gaps in leveraging institutional resources. The study identifies both strengths and limitations in students' autonomous learning development. It proposes targeted strategies—including autonomy-oriented teacher training, curriculum flexibility, learner self-assessment tools, and reflective practices—to enhance learner agency. The findings contribute to the growing body of localized research on learner autonomy in Indonesia and offer actionable implications for educators, curriculum designers, and policymakers aiming to foster lifelong learning skills in EFL contexts.